CRIMINAL LIABILITY OF PERPETRATORS OF SEXUAL VIOLENCE IN LAW NO. 12 OF 2022 CONCERNING CRIMINAL ACTS OF SEXUAL VIOLENCE - Gulo, Bestari Diberkati; sulistyawaty, Sri; Pakpahan, kartina (Jurnal Ilmu Hukum Reusam, 2024)
The accountability of perpetrators of criminal acts in Indonesia has been regulated in formal procedural instruments that have been established by the state. So far, in the process of criminal accountability in the settlement of crimes of sexual violence, there have been pros and cons in society due to the inefficiency of sanctions and fines given to perpetrators of crimes and the failure to protect the rights of victims of crimes of crimes of crimes of sexual violence. Law Number 12 of 2022 concerning Crimes of Sexual Violence exists to answer public concerns and contains rules regarding sanctions and fines as well as fulfilling the protection and rights of victims of crimes of sexual violence. The type of research used in completing this research is normative legal research. The legal sources used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The technique used in collecting data for this research is to collect secondary data consisting of primary legal materials and secondary legal materials that are related to the subject matter of the research. All research data that has been collected, analyzed using qualitative normative methods. Law Number 12 of 2022 concerning Crimes of Sexual Violenceconstitutes a complete, just, and formal foundation for perpetrators and victims of sexual violence.